Korelasi Minat Dan Hasil Belajar Siswa Melalui Penerapan Problem Solving Pada Materi Wujud Zat dan Perubahannya - Fatmalasari. L, Rizky; Latukau, Randi Hasim; Edi Saputra, I Gede Purwana; Permana, Imam; Kadir, Fitriani; Azmar, Azmar; Rahmat, Dedy (Al-Khazini: Jurnal Pendidikan Fisika, 2021)
This research is a descriptive study with a correlation type involving seventh grade  students  of  SMP  Negeri  3   Leihitu.  Research   variables,  namely variables   of   interest   in   learning   and   achievement   of   physics   learning outcomes,  while  the  data  analysis  technique  is  descriptive  analysis  and inferential  analysis  with  the  correlation  method.  The  results  of  this  study prove  that  students'  interest  in  learning  provides  a  significant  relationship with the achievement of  learning outcomes  in physics. The results  illustrate that  students'  interest  in  learning  who  is  taught  using  problem  solving methods  can  affect  student  concentration  in  learning  in  order  to  achieve learning  outcomes  outcomes  of  physics.  In  using  the  problemsolving method,  students  think  more  and  act creatively  in  solving  problems,  where the  teacher  involves  more  students  as  subjects  who  seek  and  solve  on  their own  and  not  as  objects  that  only  receive  information  from  the  teacher,  so that  students  can  actively  learn  and  appreciate  knowledge.  which  theyreceive at school in order to develop their knowledge and skills